Ontological Security, Identity, and Movement of the People: Barack Obama’s Syrian Refugee Policy - Chairunnisa, Farina; Kurniawan, Yandry (Masyarakat: Jurnal Sosiologi, 2019)
This article examines the United States’ decision to admit 10,000 Syrian refugees in the fiscal year of 2016 amidst potential national security concerns brought by the incoming refugees. In past studies, United States’ policies of refugee admission mainly focused on the security and political interests, while this particular admission decision reflected a different interest consideration, namely the ideational aspect of the United States as a nation of immigrants. Through discourse analysis on the speeches and remarks made by government actors of the United States, this research offers an alternative perspective on understanding how the United States came to a decision that may not reflect traditional security interests, but reflects its ontological security needs or its security of being. Using the framework of analysis offered by Brent J. Steele, this research finds that the United States’ awareness of its capabilities, along with past memory as a nation of immigrants and urgings from fellow international actors, affects the United States in reaching the decision to admit Syrian refugees.